In Centrifugal-Vibration Concentrators Gravitational Enrichment - Abdusamiyeva Lobarxon No‘monjon qizi; Ashirmatova Iroda Mamasaid qizi; Jo‘raqulova Sabrina Baxtiyor qizi (International Journal on Orange Technologies, 2023)
Centrifugal-vibration concentrators represent a vital tool in the field of mineral processing and ore beneficiation. This article delves into the fundamental concept of "gravitational enrichment" within these concentrators, exploring the underlying principles, operational parameters, and its significance in improving the efficiency of mineral separation. We discuss the essential keywords related to this topic and provide insights into the potential applications and future developments in this field.